Influence of the care of the self in the work of intensive care nurses - Edson José da Silva Júnior; Alexandre Pazetto Balsanelli; Vanessa Ribeiro Neves (SciELO, 2021)
ABSTRACT Objective: To analyze the influence of the care of the self in the work of intensive care nurses. Method: Qualitative study, carried out through thematic oral history. Semi-structured interviews were carried out with intensive care nurses who had worked in the area for at least one year and worked in a university hospital located in the south area of the city of São Paulo, Brazil. The script was composed by the guiding question "Does the care of the self affect your professional practice? In what way?". Other questions related to the object of study were added according to the development of each narrative. The speeches were transcribed, transcreated, and analyzed using the Content Analysis Technique. Results: 13 nurses participated in the research. The following categories emerged in their speeches: "Caring for oneself means providing safer care" and "Care of the self and the leadership of intensive care nurses". Conclusion: Practices related to the care of the self, had a positive influence on the work process of the intensive care nurse. This influence was mainly associated with patient safety and leadership development, an important managerial competence.